PSYCHOLOGICAL ASPECTS OF ENVIRONMENTAL EDUCATION AS FACTORS OF FORMATION OF ENVIRONMENTAL CULTURE OF STUDENTS HIGHER EDUCATIONAL INSTITUTIONS IN THE PROCESS OF PROFESSIONAL TRAINING - Gnilwşa, Н. В. (Pedagogy of Higher and Secondary Education, 2022)
The development problem of the essence of environmental education of future professionals is multi-faceted and should rise to a new level with the supply issue of direct communication of environmental education and identity formation.